THE EFFECT OF STORYTELLING METHODS ON THE ABILITY OF OWNING EARLY CHILDREN - Warsih; Ira Emeilia Maulidaty (Yayasan Citra Dharma Cindekia, 2021)
This study aims to determine the effect of storytelling methods on listening ability in children aged 5-6 years in TK Tunas Harapan Batokan. The purpose of this study was to test the hypothesis of the storytelling method on children's listening ability. This research method is pre-experimental design with the type of One-Group Pre-test Post-test Design. The sample of this study was 15 children (7 boys and 8 girls). The data collection techniques used were observation and documentation. The data analysis technique used statistics with t-test with SPPS 16.0 program. Hypothesis testing is done using t-test with thetechnique Independent T-test, obtained tcount of 0.000 at the significance level ???? <0.050. Thus H0 is rejected and Ha accepted for 0.000> 0.05. This proves that the storytelling method affects children's listening ability.